2011
DOI: 10.1111/j.1529-8817.2011.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Population Structure and Mating System in Chondrus Crispus (Rhodophyta)1

Abstract: Chondrus crispus Stackh. has been intensely studied, yet no study to date has elucidated its population structure or mating system despite many populations in which there was a haploid bias and lack of male gametophytes. Therefore, 12 nuclear microsatellite loci were identified in this red alga. Microsatellite markers were developed and tested against a panel of specimens collected from two shore levels at two sites in Brittany, France: Pointe de Primel and Pointe de la Jument, Concarneau. Single locus genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…Oliveira, 1986 (Guillemin et al 2008). In other species, the occurrence of sex, even occasionally, explained the lack of significant differences between haploid and diploid subpopulations: Gelidium canariensis (Grunow) Seoane Camba (Sosa & Garcia-Reina 1993); Gracilaria gracilis (Stackhouse) M. Steentoft, L. M. Irvine and W. F. Farnham 1995 (Engel et al 2004); Cladophoropsis membranacea (Hofman Bang ex C.Agardh) Børgesen, 1905(van der Strate et al 2002, and Chondrus crispus Stackhouse, 1797 (Krueger-Hadfield et al 2011). Genotyping both haploid and diploid individuals in these species is necessary to detect clonality and its effect on population structure.…”
Section: Taxonomic Knowledgementioning
confidence: 99%
“…Oliveira, 1986 (Guillemin et al 2008). In other species, the occurrence of sex, even occasionally, explained the lack of significant differences between haploid and diploid subpopulations: Gelidium canariensis (Grunow) Seoane Camba (Sosa & Garcia-Reina 1993); Gracilaria gracilis (Stackhouse) M. Steentoft, L. M. Irvine and W. F. Farnham 1995 (Engel et al 2004); Cladophoropsis membranacea (Hofman Bang ex C.Agardh) Børgesen, 1905(van der Strate et al 2002, and Chondrus crispus Stackhouse, 1797 (Krueger-Hadfield et al 2011). Genotyping both haploid and diploid individuals in these species is necessary to detect clonality and its effect on population structure.…”
Section: Taxonomic Knowledgementioning
confidence: 99%
“… Using the resorcinol test, Krueger‐Hadfield et al. () was able to assign ploidy to more individuals than were genotyped with the microsatellite loci. The sample size genotyped is provided in parantheses. …”
Section: Macroalgal Studies In Which Microsatellites Have Been Used Tmentioning
confidence: 99%
“…From a biological perspective, macroalgae have often been viewed as poor-dispersing species owing to short-lived spores and gametes [1], complex coastal topography [2], habitat discontinuities [3] and reproductive strategies and intrinsic life-history characteristics [4,5]. Studies investigating genetic structuring of macroalgae have generally demonstrated that gene flow is very limited [3,[5][6][7] and is heavily influenced by their complex life histories [4,5,7]. Gene flow in macroalgae is further influenced by landscape quality between populations in addition to geographical distance and dispersal capabilities [3].…”
Section: Introductionmentioning
confidence: 99%